(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Thoha AS, Saraswita N, Sulistiyono N, Wiranata D, Sirait SM, Inaldi R. 2022. Analysis of land cover changes due to forest fires in Gunung Leuser National Park, North Sumatra Province, Indonesia. Biodiversitas 23: 1420-1426. Forest and land fires occur almost every year with significant impacts and losses on the environment and various sectors including conservation areas. Gunung Leuser National Park (GLNP) is a conservation area in danger of losing its forest cover due to slash-and-burn land clearing. This study aimed to analyze land cover changes due to forest and land fires in GLNP of North Sumatera Province. Data of hotspots, satellite images, land cover maps, and field verification were used to see the transition of land cover changes before and after forest and land fires. Temporal and spatial analyses were carried out to see the trend of these changes. Field surveys were also conducted to verify hotspots as locations for forest fires, burned land, and human activities causing the fires. This study found that 2010 had the highest hotspots reported from 2001 to 2019. There were indications of a fairly massive forest fire in 2010, as evidenced by the identification of burned land on satellite images. The burned land was near the outer boundary of the GLNP area and expanded into the area in the following period. Before 2010, the area of the non-forest cover was not too large. After 2010, there was an increase in non-forest land cover, presumably due to increased access to enter the area after the forest was cleared after the fire. During almost 20 years, the primary dryland forest in the study area remained only 6% of the initial area. At least more than 200 ha of forest area is reduced in the study area every year. The burned lands in the following years tended to become plantation land. Plantation land cover increased by around 90% during 2000-2019 in the research sites. This study expects that GLNP management and various parties need to prevent the expansion of forest clearing because the strategic role of GLNP as a world heritage is currently in danger.